Endothelial protease-activated receptor 4: impotent or important? - Rajala, Rahul; Griffin, Courtney T. (Frontiers in Cardiovascular Medicine, 2025)
The protease thrombin, which increases its levels with various pathologies, can signal through the G protein-coupled receptors protease-activated receptors 1 and 4 (PAR1/PAR4). PAR1 is a high-affinity receptor for thrombin, whereas PAR4 is a low-affinity receptor. Finding functions for PAR4 in endothelial cells (ECs) has been an elusive goal over the last two decades. Several studies have demonstrated a lack of functionality for PAR4 in ECs, with many claiming that PAR4 function is confined mostly to platelets. A recent study from our lab identified low expressing but functional PAR4 in hepatic ECs in vivo. We also found that PAR4 likely has a higher signaling potency than PAR1. Given this potency, ECs seem to limit PAR4 signaling except for extreme cases. As a result, we claim PAR4 is not an impotent receptor because it is low expressing, but rather PAR4 is low expressing because it is a very potent receptor. Since we have finally shown PAR4 to be present and functional on ECs in vivo, it is important to outline why such controversy arose over the last two decades and, more importantly, why the receptor was undervalued on ECs. This timely review aims to inspire investigators in the field of vascular biology to study the regulatory aspect of endothelial PAR4 and its relationship with the more highly expressed PAR1.